Synthesis and Characterization of Phenylboronic Acid-Modified Insulin With Glucose-Dependent Solubility - Lin, Nai-Pin; Zheng, Nan; Purushottam, Landa; Zhang, Yi Wolf; Chou, Danny Hung-Chieh (Frontiers in Chemistry, 2022)
Glucose-responsive insulin represents a promising approach to regulate blood glucose levels. We previously showed that attaching two fluorophenylboronic acid (FPBA) residues to the C-terminal B chain of insulin glargine led to glucose-dependent solubility. Herein, we demonstrated that relocating FPBA from B chain to A chain increased the baseline solubility without affecting its potency. Furthermore, increasing the number of FPBA groups led to increased glucose-dependent solubility.